MEMAHAMI POLA KOMUNIKASI KELOMPOK ANTAR ANGGOTA KOMUNITAS PUNK DI KOTA SEMARANG - Saputra, Aditya Oktendy (Jurnal The Messenger, 2012)
Communications between members of the community in Semarang City Punk and How to use the Punk communication media in the city of Semarang by its members, in order to maintain harmony among communities. The population in this study were community members who live in areas Punk Genuk in the city of Semarang. While as many as 5 samples taken by the informant in-depth interview technique (depth-interview). The pattern of communication is known that a person's personality represents a real community members. the Punk community to gain acceptance from other members, an individual is forced to follow the pattern of communication other community members, so that communication patterns can be understood by everyone or is universal. And by using various social networking Punk community members can communicate with their comrades from other communities to get out of town, in order to maintain the relationship, strengthen kinship and closeness even though they do not have long to meet